Phase I Study Evaluating Dose De-escalation of Sorafenib with Metformin and Atorvastatin in Hepatocellular Carcinoma (SMASH). (28th February 2022) - Ostwal, Vikas; Ramaswamy, Anant; Gota, Vikram; Bhargava, Prabhat G; Srinivas, Sujay; Shriyan, Bharati; Jadhav, Shraddha; Goel, Mahesh; Patkar, Shraddha; Mandavkar, Sarika; Naughane, Deepali; Daddi, Anuprita; et al.
Abstract: Background: This phase I dose de-escalation study aimed to assess the tolerability, safety, pharmacokinetics (PK), and efficacy of sequentially decreasing doses of sorafenib in combination (SAM) with atorvastatin (A, 10 mg) and metformin (M, 500 mg BD) in patients with advanced hepatocellular carcinoma (HCC). Methods: Patients were enrolled in 1 of 4 sequential cohorts (10 patients each) of sorafenib doses (800 mg, 600 mg. 400 mg, and 200 mg) with A and M. Progression from one level to the next was based on prespecified minimum disease stabilization (at least 4/10) and upper limits of specific grade 3-5 treatment-related adverse events (TRAE). Results: The study was able to progress through all 4 dosing levels of sorafenib by the accrual of 40 patients. Thirty-eight (95%) patients had either main portal vein thrombosis or/and extra-hepatic disease. The most common grade 3-5 TRAEs were hand-foot-syndrome (grade 2 and grade 3) in 3 (8%) and transaminitis in 2 (5%) patients, respectively. The plasma concentrations of sorafenib peaked at 600 mg dose, and the concentration threshold of 2400 ng/mL was associated with higher odds of achieving time to exposure (TTE) concentrations >75% centile (odds ratio [OR] = 10.0 [1.67-44.93]; P = .01). The median overall survival for patients without early hepatic decompensation ( n = 31) was 8.9 months (95% confidence interval [CI]: 3.2-14.5 months). Conclusion: The SAM combination in HCC patients with predominantly unfavorable baseline disease characteristics showed a marked reduction in sorafenib-related side effects. Studies using sorafenib 600 mg per day in this combination along with sorafenib drug level monitoring can be evaluated in further trials. (Trial ID: CTRI/2018/07/014865). Abstract : Sorafenib is a recommended therapeutic option in advanced hepatocellular carcinoma, despite the possibility of treatment-related adverse events. This article assesses the tolerability, safety, pharmacokinetics, and efficacy of sequentially decreasing doses of sorafenib in combination with atorvastatin and metformin in patients with advanced hepatocellular carcinoma.